POTENTIAL OF GOROHO BANANA FLOUR AND TANDUK BANANA FLOUR FROM NORTH MALUKU AS ALTERNATIVE FOOD INGREDIENTS - Erna Rusliana Muhamad Saleh; Syamsul Bahri; Abu Rahmat Ibrahim (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
Goroho bananas and tanduk bananas are local bananas found in all districts/cities in North Maluku. These two types of bananas are usually consumed in North Maluku in the form of traditional foods. In order to be processed into other derivative products and to have a longer shelf life, the product innovation that can be done is to process them into banana flour. Banana flour can also be an alternative source of carbohydrates and has the potential to replace wheat flour which is still imported. So that banana flour is expected to be an alternative food ingredient. The purpose of this study was to determine the physicochemical characteristics of goroho banana flour and tanduk banana flour. In addition, this study aims to determine the potential of goroho banana flour and tanduk banana flour as alternative food ingredients. The research design used was a non-factorial Completely Randomized Design, with the treatment factor being the type of banana (goroho banana and tanduk banana). The results of the study showed that the physicochemical characteristics of goroho banana flour were 30% yield, color L 84.48, a* 1.18, b* 17.78, carbohydrate 82.91%, protein content 3.51%, total fat content 1.41%, water content 9.69%, ash content 2.50%, total energy 358.31 Kcal/100g, energy from fat 12.65 Kcal/100g and pH 5.43. The physicochemical characteristics of tanduk banana flour are yield 31%, color L 82.36, a* 2.85, b* 18.36, carbohydrate 83.69%, protein content 2.65%, total fat content 1.54%, water content 10.19%, ash content 1.94%, total energy 359.2 Kcal/100g, energy from fat 13.86 Kcal/100g and pH 6.38. The physicochemical characteristics of goroho and tanduk banana flour from North Maluku give both the potential as alternative food ingredients. Keywords: alternative food ingredients, Goroho banana flour, tanduk banana flour, North Maluku